Peran Ketua Stasi terhadap Peningkatan Partisipasi Orang Muda Katolik dalam Kegiatan Katekese di Stasi Santa Theresia Waijarang Paroki Santo Fransiskus De Sales pada Keuskupan Larantuka - Wenseslaus Ile; Antonius I. N. Tukan; Petrus Tamelab (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study is motivated by the important role of the Church as the communion of God's people in fostering and accompanying Catholic Youth (Orang Muda Katolik [OMK]) as the future generation of the Church. The Station Head (Ketua Stasi) is responsible for strengthening community fellowship, organizing pastoral activities, and mentoring Catholic youth to remain actively involved in the life of the Church. This study aims to analyze the role of the Station Head in enhancing the participation of Catholic Youth at Saint Theresia Waijarang Station. A descriptive qualitative approach was employed, with data collected through interviews and observations involving the Station Head, Catholic youth, and members of the congregation. The findings indicate that the Station Head's direct involvement in youth activities has not been fully optimized due to other professional responsibilities. As a result, some Catholic youth feel they receive insufficient attention and guidance, which affects their motivation to participate in Church activities. Nevertheless, the Station Head continues to provide support, guidance, and supervision for various pastoral programs. At the same time, Catholic youth remain actively engaged in Church activities because they recognize their responsibility as the future generation and backbone of the Church. The study concludes that effective collaboration among the Station Head, the congregation, and Catholic youth is essential for strengthening ministry, fostering faith formation, and creating an active, harmonious, and sustainable Church community.